Discourse Strategies of Administrative Communication in Selected Agricultural Research Institutes in Nigeria - Oluwafemi Jolaoso; Modupe Victoria David (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
The study critically examines the discourse strategies of administrative communication in selected agricultural research institutes in Nigeria. Twenty (20) correspondences of two of the Nigerian agricultural research institutes: Nigerian Stored Products Research Institute (NSPRI) and Cocoa Research Institute of Nigeria (CRIN) were randomly selected. Thirteen (13) of the excerpts were purposively sampled for the analysis. The data cover all selected communication outlets from the files of the selected Nigerian agricultural research institutes. Data analysis was anchored to Fairclough’s aspect of Critical Discourse Analysis. Findings reveal that thirteen (13) strategies are employed in the discourses of administrative correspondence of the selected agricultural research institutes and the strategies include command, discipline, commendation, evasive, deadline, endorsement, humility, courtesy, hierarchy, introduction, minuting, abbreviation and referencing. The study concludes the strategies were purposively deployed in the administrative correspondence of the sampled agricultural research institutes to achieve certain communicative effects.